VV-ECMO adjuvant therapy for Leptospira complicated with H1N1 infection: a case report - Zhang, YuChou; Yin, MingJing; Wen, HanChun (Frontiers in Medicine, 2025)
BackgroundLeptospirosis is an acute infectious disease that occurs by infection, progresses rapidly, and has a high mortality rate, with an estimated 1.2 million new cases and nearly 59,000 deaths each year. Due to its diverse clinical manifestations, diagnosis is often delayed. Therefore, it is necessary to pay attention to its clinical manifestations, diagnostic techniques, and treatment methods.Case reportA 51-year-old male patient from the Han ethnic group experienced fever, chills, headache, and overall fatigue after being exposed to rain, followed by yellowing of the skin and worsening of breathing difficulties. Metagenomic next-generation sequencing (mNGS) indicates infection with leptospirosis and influenza A. After 5 days of treatment with venovenous extracorporeal membrane oxygenation (VV-ECMO), Penicillium, and Oseltamivir, the condition improved.ConclusionLeptospirosis improves with VV-ECMO support and anti-infective treatment with penicillin and oseltamivir. VV-ECMO provides a therapeutic time window for rescue, and mNGS lays a foundation for early detection of etiology of leptospirosis.